PUSAT SUMBER BELAJAR GUGUS - Eva Betty Simanjuntak; Dewi Syafriani (PGSD Universitas Negeri Medan, 2018)
The partners that are targeted by this service program are the Study Center Resource Centers (PSBG) Study Centers and Creative Parks located in Tebing tinggi city of North Sumatra Province. Based on observations and interviews with the PSBG administrators there are 5 problems faced by partners, including: (1) The teacher's ability to make teaching aids and catalogs is very low; (2) The use of IT contained in the CBD is very rare; (3) RPPs made by teachers have not included various learning models; and (4) The teacher has not been able to make a monthly PSBG magazine. Based on these problems, a number of solutions were offered, including: (1) training and mentoring to create learning media and their catalogs; (2) training and mentoring for making IT-based media; (3) training and mentoring to prepare lesson plans with various learning models; and (4) training and mentoring for the creation of the PSBG monthly magazine. Specific targets and outputs that will be produced are: (1) Catalog of learning media; (2) A collection of IT-based learning media; (3) Book collection of assessment rubrics. The method of implementing the service program will be carried out in a gradual, continuous and comprehensive manner carried out through clinical supervision methods in an effort to develop the capabilities and skills of managing and empowering the sustainability of the CBC.Keywords: Revitalization, Cluster Learning Center, Based on IT